2014
DOI: 10.1080/19345747.2014.906010
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of Guided Reading and Explicit Interventions for Primary-Grade Students At-Risk for Reading Difficulties

Abstract: Considerable research evidence supports the provision of explicit instruction for students at risk for reading difficulties; however, one of the most widely implemented approaches to early reading instruction is Guided Reading (GR; Fountas & Pinnel, 1996), which deemphasizes explicit instruction and practice of reading skills in favor of extended time reading text. This study evaluated the two approaches in the context of supplemental intervention for at-risk readers at the end of Grade 1. Students (n = 218) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…This analysis shows that the web‐based ITSS made statistically significant and positive impacts on comprehension‐promoting activities such as writing a main idea and also on standardized measures of reading comprehension. The effect sizes are similar in magnitude and direction to those reported by Denton et al (), Denton, Fletcher, Taylor, Barth, and Vaughn (), Vaughn et al (), and Wanzek et al (). These research studies are used in this discussion to place our findings in the context of current research with struggling readers and targeting reading comprehension (beyond the learning to read phase).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This analysis shows that the web‐based ITSS made statistically significant and positive impacts on comprehension‐promoting activities such as writing a main idea and also on standardized measures of reading comprehension. The effect sizes are similar in magnitude and direction to those reported by Denton et al (), Denton, Fletcher, Taylor, Barth, and Vaughn (), Vaughn et al (), and Wanzek et al (). These research studies are used in this discussion to place our findings in the context of current research with struggling readers and targeting reading comprehension (beyond the learning to read phase).…”
Section: Discussionsupporting
confidence: 86%
“…Denton et al () reported effect sizes ranging from −0.18 to 1.77 on multiple reading domains with the Phono‐Graphix and Read Naturally interventions separately and effect sizes ranging from 0.84 to 1.53 on the same measures when the interventions were combined. Denton et al () found small to moderate effect sizes for explicit instruction compared with guided reading and typical school instruction on measures of decoding, comprehension, and fluency. Vaughn et al () found effect sizes of 1.2 for reading comprehension and 0.49 for word identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pupils were selected for tier 2 on the basis of initial screening, and, in many cases, a limit was set in terms of a standard reading score (e.g. less than 93 on the WJIII in Denton, Fletcher, Taylor, Barth, & Vaughn, ). Eight out of 19 were delivered outside of the regular classroom, although the exact location (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…La première caractéristique dont nous traitons concerne la priorisation des cibles essentielles. Les cibles d'un enseignement efficace de la lecture aux paliers II et III sont de la même nature que celles traitées au palier I; c'est-à-dire qu'on recommande de centrer l'intervention sur les notions, sur les habiletés et sur les stratégies qui agissent directement sur la compétence à lire et de privilégier un modèle d'enseignement systématique et explicite pour soutenir ces apprentissages (Denton, Fletcher, Taylor, Barth et Vaughn, 2014;Weiser et Mathes, 2011). Le nombre de cibles retenues aux paliers II ou III est toutefois moindre qu'au palier I. Les cibles choisies correspondent ordinairement aux habiletés les plus déficitaires chez l'élève.…”
Section: L'intensification Des Interventions Aux Paliers II Et Iiiunclassified